6y3 + 48y2 + 90y
Without any equality signs the given expression can't be considered to be equations.
6y3
3x + 6y = 363x - 6y = 0 add both equations6x = 36x = 63x - 6y = 03(6) - 6y = 018 - 6y = 018 = 6y3 = yThe solution point is (6, 3).
The greatest common factor is the lowest of the powers in this case.
Prime factor both numbers or expressions and use the factors the number of times it was used the MOST in either number. 6y^3=2*3*y*y*y 18y^4=2*3*3*y*y*y*y 2*3*3*y*y*y*y=18y^4
Yes!The word "coefficient" usually refers to the number part of a term.Some examples:The coefficient in 7x is 7.The coefficient in -2y4z3 is -2.The coefficient in b2c3d4 is 1 (because you can think of there being a '1' in front)In the polynomial x3 + 4x2y - 5xy2 + 6y3, the coefficient of xy2 is -5.Technically, you could say that in the term 27fg4, 27 is the numerical coefficient, and fg4 is the literal coefficient.
Y³-4y²-12y = y(y - 6)(y + 2) 3x³+30x²+75x = 3x(x + 5)2 5yto5-80y³ = 5y3(y + 4)(y - 4) 24to5-18y³ = 6y3(4y2 - 3) 25x to the 6th - 64 = (5x3 + 8)(5x3 - 8) 27xt³+343 = (3x + 7)(9x2 - 21x + 49) X³-64 = (x - 4)(x2 + 4x + 16)